Efforts to Increase Work Productivity through Job Training Programs Towards the Indonesian Demographic Dividend Period - Yamin, Ramadini Erlita; Sugandi, R. M.; Nurhadi, Didik (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2021)
Indonesia is predicted to experience demographic dividend from 2020 to 2030, which means that the population of productive age will be greater than the population of non-productive age, so Indonesia needs to prepare quality human resources to optimize opportunities for demographic dividend. The writing of this article aims to analyze the things that must be done by Indonesia in optimizing human resources development to face the era of demographic dividend. The research method used is descriptive qualitative. The results of this study indicate that Indonesia needs to improve and strengthen the education system to create superior human resources. Human resources development can be a solution to create superior human resources who are ready to face the era of demographic dividend, so that Indonesia can maximize opportunities to improve and strengthen the country's economy.